Population Data Information System In Rantau Kadam Village - Intan Mayang Sari; Khairil Khairil; Ricky Zulfiandry (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The development of information technology is essentially aimed at making it easier for communities to access accurate information. In the context of village administrative governance, manual population data management often causes various issues such as recording errors and inefficiency. This study aims to design and develop a web-based population information system using the waterfall development method, which includes requirement analysis, system design, implementation, testing, and maintenance. The system is built using PHP programming language, MySQL database, Visual Studio Code editor, and XAMPP server. The result shows that data recording processes become faster, more accurate, and less prone to duplication. The developed website, https://kantordesarantaukadam.online, allows population services to be efficiently performed and accessed online by village officials and residents. Hence, the system improves the quality of public services and supports the digitalization of village administrative processes.